Reconstructing Collaborative Leadership For Adaptive Educational Management In Islamic Vocational Schools - Nur Efendi (Pondok pesantren As-salafiyah As-Safi'iyyah, 2024)
This study investigates the reconstruction of collaborative leadership and its contribution to adaptive educational management in an Islamic vocational school, focusing on MA Al Ma’arif Tulungagung. The research addresses how collaborative leadership is practiced, how it supports adaptive management, and how both elements interact within the institutional context. A qualitative case study design was employed to explore experiences of the principal, teachers, and administrative staff. Data were collected through semi-structured interviews, observations, and document analysis, followed by thematic analysis. The findings reveal that collaborative leadership is enacted through participatory decision-making, shared responsibility, and open communication, which strengthen coordination and institutional responsiveness. Adaptive educational management is reflected in flexible planning, contextual instructional practices, and continuous evaluation processes that respond to changing demands. The interaction between leadership and management forms a cyclical process where collaboration supports adaptability and feedback informs leadership refinement. This study concludes that reconstructing collaborative leadership strengthens institutional capacity to sustain adaptive management while maintaining alignment with Islamic values and vocational education goals.